2017
DOI: 10.2139/ssrn.3062941
|View full text |Cite
|
Sign up to set email alerts
|

Can Outsourcing Improve Liberia's Schools? Preliminary Results from Year One of a Three-Year Randomized Evaluation of Partnership Schools for Liberia

Abstract: After one year, public schools managed by private contractors in Liberia raised student learning by 60 percent, compared to standard public schools. But costs were high, performance varied across contractors, and contracts authorized the largest contractor to push excess pupils and underperforming teachers onto other government schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…The three-year randomised control trial, conducted by an independent entity, shows encouraging preliminary (year-one) results (Romero, Sandefur & Sandholtz, 2017). Students in LEAP schools learned 60 per cent more than the students in non-LEAP schools, student attendance improved by 10 per cent and teachers were 20 per cent more likely to be in school than their counterparts elsewhere.…”
Section: Liberian Education Advancement Program (Leap)mentioning
confidence: 98%
“…The three-year randomised control trial, conducted by an independent entity, shows encouraging preliminary (year-one) results (Romero, Sandefur & Sandholtz, 2017). Students in LEAP schools learned 60 per cent more than the students in non-LEAP schools, student attendance improved by 10 per cent and teachers were 20 per cent more likely to be in school than their counterparts elsewhere.…”
Section: Liberian Education Advancement Program (Leap)mentioning
confidence: 98%
“…There is a recent prominent example, in Liberia, of a more radical experiment to improve quality by outsourcing delivery of schools to the private sector (Romero et al, 2017). An evaluation after one year noted that children in the private schools had done better than those in the public schools, but questioned if these gains could be maintained at scale without changes in the model.…”
Section: Private Schoolsmentioning
confidence: 99%
“…Under the outsourcing scheme, school admission is free, PSL teachers are paid by the government, and contractors cannot screen students by ability or other characteristics. Romero, Sandefur, and Sandholtz (2017) conducted a randomized evaluation of the project and found that contracted schools performed significantly better than regular public schools one year after the intervention, with higher teacher attendance and better student performance in English and math. However, one provider, Bridge International Academies, pushed excess students and worse-performing teachers to government-run schools, subverting policymakers' efforts to maximize access to quality education.…”
Section: A Role For the Domestic Private Sectormentioning
confidence: 99%